Prevalence and management of prehypertension and hypertension by geographic regions of Thailand: The Third National Health Examination Survey, 2004 - Aekplakorn W. (2014)
OBJECTIVE: To determine the prevalence of prehypertension and hypertension, and management of hypertension, by geographic regions of Thailand. METHODS: Using a stratified, multistage sampling design, data from a nationally representative sample of 39 290 individuals aged ≥15 years were collected by interview, physical examination and blood sample. RESULTS: The prevalence of hypertension and prehypertension weighted to the national 2004 population was 22.0% [95% confidence interval (CI) = 20.5-23.6] and 32.8% (95% CI = 31.5-34.1), respectively, with a higher prevalence in men compared to women. Hypertension was more common in urban compared to rural men, but similar between urban and rural women. Despite some variation, the prevalence of hypertension and prehypertension was relatively uniform across geographical regions. Of those identified as having hypertension in the survey, 69.8% (95% CI = 67.8-71.7) were unaware that they had hypertension. Although the majority of those who were aware (78.2%; 95% CI = 75.8-80.5) had taken blood pressure-lowering drugs in the last 2 weeks, of these only 36.6% (95% CI = 33.3-40.0) had blood pressure < 140/90 mmHg. Rural populations and those from the economically poorer Northeast region were more likely to be unaware that they had hypertension. CONCLUSION: Compared to previous surveys, the prevalence of hypertension and prehypertension is rising rapidly, and is spread relatively evenly across regions of Thailand. Levels of awareness of hypertension were low across the country. A challenging task remains in improving screening, treatment and control of hypertension at the same time as promoting healthier lifestyles. © 2008 Lippincott Williams & Wilkins, Inc.